Cooperation and Conflict in Occupational Safety and Health: A Multination Study of The Automotive Industry - Lewchuk, Wayne (Labour / Le Travail, 1991)
The article reviews the book, "Cooperation and Conflict in Occupational Safety and Health: A Multination Study of The Automotive Industry," by Richard E. Wokutch.
Keywords: BOOKS -- Reviews; COOPERATION & Conflict in Occupational Safety & Health: A Multination Study of the Automotive Industry (Book); Industrial safety; Nonfiction; WOKUTCH, Richard E.